2016
DOI: 10.1200/jop.2015.007385
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Oncology Practice: Adjusting to a New Reimbursement Model

Abstract: The move to hypofractionation in the United States will lead to increased pressures on departments to address budget shortfalls resulting from the decrease in per-patient revenue. This may be done through a combination of an increase in patient volume, recognition of the increased skill sets required to deliver hypofractionated radiotherapy, delay in capital purchases, and/or reduction in staff. In a value-based environment, these evolutions should improve the value proposition of radiation oncology over a fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…In 2010, 64% of radiation oncologists in the United States had access to equipment sufficient for the application of hypofractionation techniques. Research suggests that uptake of hypofractionation across the United States in 2011 was observed in 8% of prostate cancer patients, 44% of inoperable lung cancer patients and 20–35% in the setting of breast cancer . In contrast, the uptake figures across Canadian breast cancer patients is currently estimated at 70%; perhaps reflecting differences in practice attributed to varying models of health care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2010, 64% of radiation oncologists in the United States had access to equipment sufficient for the application of hypofractionation techniques. Research suggests that uptake of hypofractionation across the United States in 2011 was observed in 8% of prostate cancer patients, 44% of inoperable lung cancer patients and 20–35% in the setting of breast cancer . In contrast, the uptake figures across Canadian breast cancer patients is currently estimated at 70%; perhaps reflecting differences in practice attributed to varying models of health care.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable evidence to support the use of hypofractionation in the setting of lung cancer and palliation. Extreme hypofractionated regimens for lung cancer offer favourable outcomes with a cost‐effective and less invasive procedure than surgery and associated hospitalisation . Furthermore, multiple studies across Europe and the USA have demonstrated an equivalent outcome in hypofractionated palliation compared with conventional approaches – though this technique is heavily underutilised …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current fee-forservice reimbursement paradigm in radiation oncology misaligns incentives by rewarding longer courses of radiation. Konksi et al (52) showed that if a radiation therapy department treated 40% of its breast cancer patients with hypofractionated therapy, annual revenue would decrease by over $500,000. Alternate reimbursement models that incentivize greater adherence to evidence-based recommendations could help reduce both physician-based and practice-based variability while improving quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…The UK and Canada have seen far broader adoption of HF-WBI (around 80% and 71%, respectively) (18,19), which can in part be attributed to the UK’s nationalized adoption of HF-WBI and Canada’s more flexible use of fee-for-service payments. It is estimated that a US hospital-based practice’s adoption of a 70% HF-WBI rate would result in annual reductions of $300,790 in technical revenues and 731 professional RVUs with current reimbursement policies (20), representing significant proportions of total practice income; therefore, it is not surprising that variation in HF-WBI utilization has been found to be related more to individual provider characteristics than clinical or demographic characteristics (21). …”
mentioning
confidence: 99%